The Vulnerability of African Countries to Oil Price Shocks : Major Factors and Policy Options, The Case of Oil Importing Countries - Bacon, Robert (World Bank, Washington, DC, 2014)
Apart from a few oil exporters, Sub-Saharan Africa consists of a large number of low-income countries, many of which are highly dependent on oil imports as a source of primary energy. The purpose of this study is to provide information on a number of aspects of energy and oil use in these countries, with a view to highlighting the vulnerabilities of the different countries against sustained or even increasing oil prices, and explore some of the policy implications. The topics investigated are: 1) How vulnerable is each country at present to a sustained oil price rise measured in terms of the ratio of net oil imports to gross domestic product (GDP), and in terms of its ability to pay as indexed by the ratio of net external debt to GDP? 2) What are the energy and oil intensities of the economies and what are the recent trends (measured by the ratio of energy use to GDP)? Can countries expect that energy and oil intensity will rise or fall as the level of development improves? 3) What is the oil fuel dependence of the economy, and what is its recent history (measured as the share of the use of oil and oil products in total primary energy use)? What has been the pattern of use of other fuels? What distinguishes Africa from other regions is its almost complete reliance on imported oil (apart from the net oil exporters) and its very high oil fuel dependence for its primary energy consumption besides biomass. This report shows that net oil importing countries of Sub-Saharan Africa are highly vulnerable to oil shocks, have the highest ratio of external debt to GDP and the lowest per capita income.